Some changes of psychologic status of patients having multipled sclerosis - Ye. V. Alekseyenko; O. S. Sysoyeva; I. V. Smagina; S. A. Fedyanin (Бюллетень сибирской медицины)
There are psychologic status of patients having multipled sclerosis research results. 30 patients were involved in the research, among them there were 18 (60%) female and 12 (40%) male ones at the age between 20 and 60. Patient examination was realized by means of the Spielberger, Maudsley and Zung methods. As a result of research there are patient's psychological state changes. 66% of patients have these changes in the form of high-grade uneasiness, 50% — in the form of rigidity and introversion, 83% have depressing disorders in the form of slight depression and subdepression.These findings expand our conception about psychological mechanisms of dissociated personality patients with multipled sclerosis have, and need various multimodal approaches for their psychological correction.